2
$\begingroup$

Cauchy Product:

Let $c_n$ be $$\left(\displaystyle\sum a_n\right)\left(\displaystyle\sum b_m\right)=\displaystyle\sum c_k\tag1$$

Then;

$$c_k=\sum_{m+n=k}a_n b_m=\displaystyle\sum_{n=0}^k a_n b_{k-n}\tag2$$

We know that;

$$\sin x=\sum_{i=0}^\infty\dfrac{(-1)^i(x)^{2i+1}}{(2i+1)!},\quad\cos y=\sum_{i=0}^\infty\dfrac{(-1)^i(y)^{2i}}{(2i)!}\tag3$$

Let $a_n,b_m$ be

$$a_n=\dfrac{(-1)^n(x)^{2n+1}}{(2n+1)!},\quad b_m=\dfrac{(-1)^m(y)^{2m}}{(2m)!}\\\text{ }\\\sum (sincos)_k=\sin x\cos y \\ \text{ }\\ \sum(cossin)_k=\cos x\sin y\tag4$$

From $(2)$ we know that we can this;

$$(sincos)_k=\displaystyle\sum_{n=0}^k a_n b_{k-n}=\sum_{n=0}^k\dfrac{(-1)^n(x)^{2n+1}}{(2n+1)!}\dfrac{(-1)^{k-n}(y)^{2(k-n)}}{(2(k-n))!}\tag5$$

And

$$(cossin)_k=\displaystyle\sum_{n=0}^k a_n b_{k-n}=\sum_{n=0}^k\dfrac{(-1)^n(y)^{2n+1}}{(2n+1)!}\dfrac{(-1)^{k-n}(x)^{2(k-n)}}{(2(k-n))!}\tag6$$

And since our definitions $\sin x\cos y+\sin y\cos x=I$ equals to ;

$$I=\displaystyle\sum_{k=0}^\infty\left[\sum_{n=0}^k(-1)^n\left(\dfrac{(x)^{2n+1}(y)^{2(k-n)}+(y)^{2n+1}(x)^{2(k-n)}}{(2n+1)!(2(k-n))!}\right)\right]\tag7$$

,

$$I=\displaystyle\sum_{k=0}^\infty\left[\sum_{n=0}^k(-1)^n\left(\dfrac{\frac{x^{2n+1}y^{2k}}{y^{2n}}+\frac{y^{2n+1}x^{2k}}{x^{2n}}}{(2n+1)!(2(k-n))!}\right)\right]\\=\displaystyle\sum_{k=0}^\infty\left[\sum_{n=0}^k(-1)^n\left(\dfrac{x^{4n+1}y^{2k}+y^{4n+1}x^{2k}}{(xy)^{2n}(2n+1)!(2(k-n))!}\right)\right]\tag8$$

I couldn't go any further,please tell whether I make mistake or not?How we can prove more quickly and are there any methods to prove this equation?How we can use this "Cauchy Product" method correctly and accurately?

$\endgroup$
  • 1
    $\begingroup$ you can try to find when y is fixed, the Fourier serie for sin(x+y). $\endgroup$ – zwim Apr 3 '17 at 23:15
  • 2
    $\begingroup$ Note that from (7) you can change the inner sum to $\sum_{m=0}^{2k+1}(-1)^n\frac{x^my^{2k+1-m}}{(m)!(2k+1-m)!}$ $\endgroup$ – Mosquite Apr 3 '17 at 23:19
  • $\begingroup$ @Mosquite can you please gıve more ınformatıon, I couldn't sımply change into this term $\endgroup$ – user2312512851 Apr 7 '17 at 22:48
  • $\begingroup$ and can you gıve me furtherreading about, how we can change index of sums ? $\endgroup$ – user2312512851 Apr 7 '17 at 22:48
  • $\begingroup$ ? please, I couldn't do. $\endgroup$ – user2312512851 Apr 13 '17 at 19:30
4
$\begingroup$

I can't help you with the Cauchy Product, but here's an alternative proof for the identity:

By Euler's formula, $$e^{i(\alpha+\beta)}=\cos(\alpha+\beta)+i\sin(\alpha+\beta)$$ On the other hand, $$e^{i(\alpha+\beta)}=e^{i\alpha}e^{i\beta}=[\cos(\alpha)+i\sin(\alpha)][\cos(\beta)+i\sin(\beta)]$$$$=\cos(\alpha)\cos(\beta)+i\cos(\beta)sin(\alpha)+i\cos(\alpha)\sin(\beta)-\sin(\alpha)\sin(\beta)$$ Equate real and imaginary parts. This also yields the corresponding identity for cosine. Incidentally, many handy trig identities follow from Euler's formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.